2001
DOI: 10.1046/j.1432-1327.2001.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of the c‐erbB2/neugene upregulates the expression of sialyl Lewis X, α1,3‐fucosyltransferase VII, and metastatic potential in a human hepatocarcinoma cell line

Abstract: The pCMV4 plasmid containing the cancer-promoting gene, c-erbB2/neu, was cotransfected into the human hepatocarcinoma cell line 7721 with the pcDNA3 vector, which contains the`neo' selectable marker. Several clones showing stable expression of c-erbB2/neu were established and characterized by determination of c-erbB2/neu mRNA and its encoded protein p185. Expression of Lewis antigens and a1,3-fucosyltransferases and the biological behavior of 7721 cells after c-erbB2/neu transfection were studied using mock ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
61
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…Increased expression of UDP-galactose transporter gene (UGT1) in cancers was also suggested to be involved in the induction of these selectin ligands, because the introduction of the gene for UDP-galactose transporter conferred the induction of sialyl Lewis a and sialyl Lewis x expression on cultured cancer cells (8). Other investigators have suggested a role for fucosyltransferase VII (9)(10)(11) and even the involvement of another sugar transporter, GLUT1, for induction of sialyl Lewis x in cancers (12). However, the exact mechanism underlying this transcriptional induction has remained uncharacterized.…”
mentioning
confidence: 99%
“…Increased expression of UDP-galactose transporter gene (UGT1) in cancers was also suggested to be involved in the induction of these selectin ligands, because the introduction of the gene for UDP-galactose transporter conferred the induction of sialyl Lewis a and sialyl Lewis x expression on cultured cancer cells (8). Other investigators have suggested a role for fucosyltransferase VII (9)(10)(11) and even the involvement of another sugar transporter, GLUT1, for induction of sialyl Lewis x in cancers (12). However, the exact mechanism underlying this transcriptional induction has remained uncharacterized.…”
mentioning
confidence: 99%
“…Other reagents, including dNTP, oligo (dT)-18, enhanced chemiluminescence (ECL) reagent and g-32 P-ATP (5 mCi/pmol) were commercially available in China. The H7721 cell line transfected with a-1,3-FucT-VII was established in our laboratory as previously reported [10]. Two transfectants were selected: one expressed a high level of a-1,3-FucT-VII mRNA and was named as FucTVII-H, another expressed moderate mRNA of a-1,3-FucT-VII and was designated FucTVII-M. H7721 cells mock-transfected with the empty vector pcDNA3.1 were used as the control, which expressed a low level of a-1,3-FucT-VII mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has demonstrated that surface SLe x is a metastasis-related sugar structure. It was increased on H7721 human hepatocarcinoma cells after transfection of the metastasis-promoting gene c-erbB2/neu [10], or treatment with epidermal growth factor [11], whereas it was decreased by the metastasis-suppressive gene nm23H1 [12] or all-trans retinoic acid [11]. The metastatic potential, including cell adhesion to laminin, cell migration through a transwell and cell invasion through a matrigel, was always positively correlated to SLe x expression on the cell surface [10 -12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer cell lines were cultured at 37°C, 5% CO 2 in RPMI-1640 medium supplemented with 10% fetal calf serum, penicillin and streptomycin, as described by our laboratory [25]. …”
Section: Methodsmentioning
confidence: 99%